Clinical anatomy for dummies - Terfera, David; Jegtvig, Shereen (Hoboken, N.J. : John Wiley [distributor], 2012)
The authors focus on specific structures and issues that people may encounter in a clinical setting, to present a friendly, unintimidating overview of the material covered in a typical college-level clinical anatomy course.
Beginning with clinical anatomy basics -- Understanding the thorax, abdomen, and pelvis -- Looking at the head, neck, and back -- Moving to the upper and lower extremities -- The part of tens.
Keywords: Anatomy